Адаптація комунальної теплоенергетики до змін клімату - Басок, Б.І.; Базєєв, Є.Т.; Кураєва, І.В. (Вісник НАН України, 2021)
Помітний тренд підвищення глобальної температури, зафіксований з середини ХХ ст., який особливо посилився на початку ХХI ст., змусив наукове співтовариство розпочати активне обговорення можливих шляхів
подальшого розвитку ситуації з глобальним потеплінням, її наслідків та
проблем, пов’язаних з адаптацією до змін клімату. Проблема адаптації до
глобального потепління стосується різних галузей економіки і сфер життєдіяльності людини, зокрема й комунальної енергетики. Тому в установах Відділення фізико-технічних проблем енергетики НАН України створено
інноваційні енергоефективні технології, орієнтовані на пом’якшення наслідків змін клімату, в тому числі й з використанням відновлюваних джерел енергії, а також розроблено обладнання для інженерних систем енергозабезпечення будівель житлово-комунальної сфери. Оптимізовано архітектурно-будівельні рішення, що дозволяє знизити обсяги використання енергоресурсів і тим самим зменшити викиди парникових газів. The instrumentally recorded trend of global temperature growth since the middle of the twentieth century due to rising
greenhouse gases in the Earth's atmosphere (mainly CO2, CH4, N2O) has exacerbated the problems of adaptation to
climate change in various sectors of the economy and human life. Problems. Adaptation to global warming also applies
to communal energy. Climate change necessitates a review of both heating and air conditioning in housing and communal
services. It is necessary to develop measures and mechanisms, the implementation of which will guarantee economically
justified comfortable and reliable heat and cold supply of buildings and structures during climate change. Purpose. Development
of measures and mechanisms adapted to climate change in the application of engineering systems for energy
supply of energy efficient buildings, mainly with the use of renewable energy sources. Materials and methods. Analytical
and experimental studies of heat transfer and monitoring of thermal regimes in the enclosing structures of buildings were
carried out with the development of innovative energy-efficient engineering systems of energy supply demonstration,
passive house type "zero-energy" (total area of four-storey building - 306 m2) using modern computers. means of diagnostics
of indicators of thermal characteristics of enclosing designs and engineering systems. Results. Experimental developments
of innovative energy-efficient technologies and equipment of energy supply systems of buildings were performed
and their architectural and construction designs were optimized, which allowed to reduce energy use (taking into
account their full production life cycle) and, as a result, reduce greenhouse gas emissions. In order to expand and deepen
the theory and practice of improving the energy efficiency of buildings in the near future, the scientific priority and subject
of basic and applied research have been identified. Conclusions. Developed adaptive to climate change innovative
energy efficient technologies and equipment of engineering systems of energy supply of buildings using renewable energy
sources and modern architectural and construction solutions can be used in the practice of energy supply of buildings of
housing and communal services.